Resilience against early-life stress in female rodents is captured in dendritic morphology of basolateral amygdala - Lee, Yan Jun (2015)
The increasing prevalence of early-life stress (ELS) in recent years and the fact that it has been shown to increase the susceptibility to develop psychopathologies in adulthood have spurred numerous studies to investigate the relations between ELS and emotional regulation. Since basolateral amygdala (BLA) is crucial for mood regulation and involved in the neural circuitry mediating stress responses, BLA disruption is a potential underlying mechanism for the emergence of these neuropsychiatric disorders. Despite this, there were limited studies on the effects of ELS on the neuronal morphology of BLA. Moreover, the plausible confounding effect by estradiol often results in the exclusion of female subjects, albeit significant gender-specific differences in stress responses were demonstrated. Therefore, we examined the effects of ELS, in the form of maternal separation (MS), on the dendritic architecture of BLA neurons in female rats. We revealed no significant alterations in the total dendritic length and number of branch points in BLA neurons following MS. We further speculated the involvement of estradiol in maintaining the hippocampal plasticity and basal corticosterone levels, thereby accounting for the unaltered BLA plasticity in females. This study serves as a start in probing the vast possibilities that account for the resilience against ELS.